Application of energy saving fins on rudders - Falkenhorst, Arne; Krüger, Stefan; Steinbach, Christoph (ASME, 2015)
Due to rising fuel oil prices in the last decade as well as rising design speeds, it has become common practice to build rudders with twisted leading edges to minimize resistance and cavitation risk. The next step in this development is the application of fins on to the rudder. The aim is to generate a distinct amount of thrust through the fins by retrieving rotational kinetic energy from the propeller slipstream. This paper presents a fast method to design and calculate rudder fins in the propeller slipstream, which has been implemented in the ship design environment E4. Because of his working principle, the propeller induces velocities to its slipstream. In the usual setup, the rudder is placed behind the propeller to generate higher steering forces caused by the higher inflow speed in the slipstream. In this arrangement, propeller and rudder together are forming a rotor - stator system. The gains of the stator can be maximized by adding fins to the rudder. The main challenge of a fin design is the maximization and prediction of the regained thrust from the propeller slipstream. In order to do this, a steady, three dimensional, direct panel method is used to calculate the flow around the rudder and fin bodies, from which later the pressures and forces are evaluated. A lifting line method is used to predict the inflow velocities caused by the vortex dominated propeller slipstream on each panel. A special focus is on the treatment of the vortex wake, as crossing wake elements can lead to numerical instabilities and a wrong wake alignment produces bad thrust predictions. For the purpose of rudder design steady computation should be preferred over fully unsteady computation, since only time average integral values are of interest and the degrees of freedom are reduced to the relevant ones. For example, it is not necessary to know the fluctuation of the angle of attack for the basic design of the profile respective the leading edge of the foil, only the mean value is needed. In the industrial practice, rudder fins ...